Romanticism in Poetry of Surat Cinta by WS Rendra - Takwa Takwa; Agus Nasir; Abdul Jumail Syam (Journal of Indonesian Language Education and Literary, 2019)
This research is motivated by a theory that combines daily reality and the reality behind it and tries to find daily reality, but on the other hand it also tries to discover what is behind daily reality. The problem under study is how romanticism in the poems of Surat Cinta by WS Rendra. The purpose of this study is to describe romanticism in the poem Surat Cinta by WS Rendra. The method used is descriptive qualitative. The data source of this research, namely the poem Surat Cinta by WS Rendra. The research instrument was the researcher himself, with data collection techniques carried out by reading and writing techniques. The technique is carried out in the following sequence (1) reading poetry, (2) recording the entire data obtained from the reading results, and (3) identifying the problem points according to the scope of the study. Data analysis techniques are processed through an expressive approach that focuses attention on the authors of literary works. The results showed that there was an equivalent and opposition in the poem Surat Cinta by WS Rendra. Equivalent can be found in aspects of love that lead to: (1) passion, (2) liking, (3) remembering and thinking in the heart, (4) distress, (5) worry, and (6) sadness. Meanwhile, the Opposition can be found in aspects of expression in the form of: (1) thoughts with feelings, (2) men with women, (3) likes with grief, and (4) sweet with bitter. Equivalent and opposition in the poem Surat Cinta by Rendra as a whole develops the integrity of meaning in poetry.